Bioaccumulation and biomagnification of potential toxic elements (PTEs): An Avicennia germinans-Uca rapax trophic transfer story from Jobos Bay, Puerto Rico - Martinez-Colon, Michael; Alegria, Henry; Huber, Ashley; Gül, Hatice Kübra; Kurt Karakuş, Perihan Binnur (Elsevier, 2021)
In southern Puerto Rico along the coastline bordering the Jobos Bay National Estuarine Research Reserve, environmental encroachment has exposed mangrove forest to different sources of pollution. Potentially toxic element concentrations from the F1(Tess) (exchangeable), F4(Tess) (oxidizable), mangrove leaf litter (MLL), and fiddler crab whole body soft tissue were analyzed to assess the fate and transport of pollutants from the environment and its transition into flora-fauna via trophic transfer. Geo-accumulation factor values suggest the bay has experienced limited to no pollution when combining the concentrations of potentially toxic elements extracted from the F1(Tess) and F4(Tess) sediment fractions. These geochemical sedimentary compartments are considered "bioavailable" to flora-fauna as evidenced by the bioaccumulated Cd-Ba-V-Cu-Zn-As-Se in the leaf litter of the black mangrove Avicennia germinans and in the fiddler crab Uca rapax. The biota-sediment accumulation factor (F1(Tess) + F4(Tess)) demonstrated that Uca rapax behave like a de-concentrator for most pollutants and as a macro-concentrator for Cu-As, while the bioconcentration factors identified only Cu-As-Se as being actively bioaccumulated in the fiddler crabs. Of all the potentially toxic elements studied, As is the only one to be biomagnified via sediment-Avicennia germinans leaf litter-Uca rapax food chain. An unexpected find of this study was that the excavated sediment "pellets" by Uca rapax contained up to 4x the concentrations of Cd-Ba-V-Cr-Co-Ni-Cu-Zn-As-Se when compared to the F1(Tess) sediment fraction from the surface, thus suggesting a variable redox boundary within the fiddler crab's burrow.
Keywords: Pollution; Caribbean; Fiddler crab; Heavy metals; Black mangrove